Formation and Change of Beliefs through Online Environments: Analysis on the “Diyanet English” X Account - Ahmet Koçyiğit (Medya ve Din Araştırmaları Dergisi)
This study focuses on the formation and change of religious beliefs in the age of social media. Accordingly, this study aims to determine how social media is used in religious contexts. Another aim of the study is to reveal how the formation and change processes of religious beliefs are realized through social media tools. In line with these objectives, the official X account of the Presidency of the Republic of Türkiye - Presidency of Religious Affairs named "Diyanet English", which shares posts in English, was analyzed using the content analysis method. The posts made from this account between July 1, 2023 and July 1, 2024 were analyzed for the aim of the study using the MAXQDA 2022 package program. The data obtained within the framework of the analysis were coded and the subject distribution, sub-codes, and word cloud of the shared content were presented. When the findings and results obtained in the study were evaluated, it was determined that the Presidency of Religious Affairs shared mostly religious information, official statements, and content related to social and communal issues from the account in question. In addition, it was concluded that this account is not used actively, the posts were limited, and there was a lack of interactive use.